Role of Informed Consent in India Past, Present and Future Trends - Yadav, Mukesh; Thakur, Pramendra Singh; Rastogi , Pooja (Journal of Indian Academy of Forensic Medicine, 2015)
There is a need to keep the cost of treatment within affordable limits. Bringing in the American  concepts and standards of treatment procedures and disclosure of risks, consequences and choices will  inevitably bring in higher cost-structure of treatment. Patients in India cannot afford them. People in India  still have great regard and respect for Doctors. The Members of medical profession have also, by and  large, shown care and concern for the patients. There is an atmosphere of trust and implicit faith in the  advice given by the Doctor. Apex Court observed that “What choice do these poor patients have? Any  treatment of whatever degree is a boon or a favour, for them. The stark reality is that for a vast majority in  the country, the concepts of informed consent or any form of consent, and choice in treatment, have no  meaning or relevance.” This paper deals with the applicability of concept of ‘informed consent’ in past, present and  future scenario in India, based on the critical review of recent decisions of Hon’ble Supreme Court of India  and National Consumer Dispute Redressal Commission, New Delhi.
Keywords: Consent; Real Consent; Informed Consent; Oral Consent; Deficiency of Service